Who in Ireland speaks and understands Russian? - Smyth, Sarah (Trinity College Dublin. Long Room Hub, 2008)
This is a research project on cultural and linguistic diversity, drawing on the experience of people in Ireland who speak and understand Russian.
Exhibited at the Glucksman Memorial Symposium on June 12th 2008
Keywords: Russian language; Ireland -- languages in